Forests for people : International Year of Forests 2011 (Tudor Rose LeicesterGB, 2012)
Showcases articles and stories from around the world, reflecting how people are changing their interaction with forests to sustainably manage these vital resources. Stresses that people directly depend on forests for their well-being and even survival. Emphasises the fact that forests are at the centre of our existence, from mitigating climate change to providing wood, medicines and the livelihoods of billions of people from across the world. Features a range of international speakers, including Secretary-General of CARICOM, Amb. Irwin Larocque.
Keywords: FORESTS